A double line SIW cavity backed antenna for WLAN applications. Issue 9 (26th May 2019) - Anand, Swaminathan; Rokhini, D.
Abstract: A compact double line substrate integrated waveguide (DLSIW) cavity backed antenna is realized using half mode SIW technology for WLAN applications. The existing single line SIW antennas for WLAN applications have low gain and less efficiency. To overcome this limitation, DLSIW structure is proposed. The new DLSIW structure simultaneously achieves better gain, radiation efficiency, and good front to back ratio (FTBR) with compact size. To improve the FTBR, ground extension is made. The size reduction of the proposed design is implemented with half mode SIW topology. The gain and efficiency improved new DLSIW antenna is fabricated using FR4 material and it resonates at 5.27GHz WLAN frequency. The size of antenna is 44 mm × 18.75 mm × 1.6 mm and it has the gain of 5.824 dB. The radiation efficiency and FTBR of the antenna are 69.13% and 13.65 dB, respectively. The design is experimentally tested and compared with earlier WLAN antennas. There is a better accordance between simulated and measured results.